ANALISA DU-PONT UNTUK MENINGKATKAN RETURN ON ASSETS (ROA) PT INDOFOOD CBP SUKSES MAKMUR Tbk - , (Politeknik Sawunggalih Aji, 2021)
PT Indofood CBP Sukses Makmur Tbk is one company in Indonesia which is engaged in food and beverages. One main goal is making a profit or profit as much as possible. Based on the information of net sales in 2012 and 2013 from the income statement Indofood CBP Sukses Makmur Tbk, generated net sales in 2013 increased compared to the previous year, but operating profit and profit for the year declined. This suggest that the increase in sales volume is not the only factor that can increase company profit in a period. There are various other factors that can affect. Du-pont analysis serves to calculate the Return On Assets (ROA) generated from each period and determine what factors that can affect the magnitude of the Return On Assets (ROA). Du-pont analysis to calculate Return On Assets (ROA) was applied and calculated using Microsoft Excel 2007 based accounts automatically terinputkan of Statements of Financial Position and Comprehensive Income. This analysis consists of seven calculations that include Return On Assets (ROA), Profit Margin, Net Operating Income, Total Expenses for Operations, Investment Turnover, Total Investment and Working Capital. As a result, it can be seen how the rate of return on assets (ROA) in 2011 to 2013 as well as the magnitude of each calculation in each period to be seen what factors increase or decrease from the previous period, so it can be used as a record for the company to then be increased or reduced in value to further increase the ROA in the future. Keywords : Du-pont Analysis, Return On Assets (ROA)